Sex Differences of Cephalic Index among Nepalese Medical Students - Shrestha, Subina; KC, Sudikshya (Nepal Journal of Health Sciences, 2024)
Introduction: Anthropometry is used to measure the morphological parameters. Among the anthropometric variables, cephalic index is one of the important tools which help to determine the geographical sex, age and racial variations. Cephalic index is calculated as maximum head breadth (MHB)/maximum head length (MHL)*100.Objective: The aim of this study was to find out whether sex could be determined by using cephalic index.Methods: The study included all the students of Madan Bhandari Academy of Health Sciences, among them 80 were male and 123 were female. The head length and head breadth were measured by using the instrument, spreading caliper, inhe department of Anatomy, which included students without any visible craniofacial skeleton deformities and students with the age of 18 to 25 years. The exclusion criteria were students with previous history and existing history of craniofacial trauma.Results: The mean head length of male was 18.036±1.02 while mean breadth was 14.161±0.869 Similarly, the mean length of female was 17.264±1.002 and mean breadth was 13.635±0.803. The mean cephalic index of male and female were 78.723±5.986 and 79.218±5.847 respectively. The male head length was 0.772cm more than female being statistically significant (p=0.045